Offset policies (compensations) : general issues and case study of Africa’s offset system - (:unkn) unknown (My University, 2016)
Offsets arrangements in government procurement are discriminatory policy tools aimed at increasing local production. They reflect a transfer or a creation of new activities as a pre-condition to the validity of the purchasing contract. The governments use these mechanisms to encourage local development or to improve the balance-of-payments. In spite of the broad utilization of offset practices, they are relatively unknown and little described in academic literature. The goal of this thesis is to define, to explain and to assess the importance of these practices in the international trade and to provide a theoretical framework within which it will be possible to critically appraise the success of an offset policy (its effectiveness and efficiency) for host countries. In order to take into account the success factors for an offset policy, the relationship between the host country and the obligor as well as the result of this relationship is examined through the game theory approach. By applying this general framework to the study of South African Offset policy and more particularly to the evaluation of 121 civil offset projects provided between 1996 and 2012, under the Strategic Defense Package purchase we find the following results: at the conclusion of public procurement contracts, South-African offset projects hold out promises of important economic benefits for the country. Nevertheless, during the implementation process, many violations of rules and procedures decrease the positive impact of these projects and hinder their effectiveness. The lack of transparency in the negotiation process, the selection and the execution phase of offset projects show that South Africa did not obtain best value for public money. It is difficult to appraise global program efficiency because of lack of data and analysis problems. However the estimated impact remains positive.
Keywords: African Research